Photoswitchable Catalytic Aerobic Oxidation of Biomass-Based Furfural: A Selective Route for the Synthesis of 5‑Hydroxy-2(5H)-furanone and Maleic Acid by Using the CdS/MOF Photocatalyst - Saki, Saeede; Hosseini-Sarvari, Mona; Gu, Yanlong; Zhang, Tianjian (Industrial & engineering chemistry research, 2024)
Selective oxidation of furfural has become important for the synthesis of pharmaceutical intermediates and chemical industries. The development of effective methods for biomass valorization is a very attractive subject. Here, we performed an initial investigation into the photocatalytic selective oxidation of furfural to maleic acid (MA) as a valuable chemical and the vital bioactive intermediate 5-hydroxy-2(5H)-furanone (HFO). In this work, MOFs-based Ti (NH2-MIL-125) was modified with the easy method by introducing the proper amount of CdS (2.5%) on the surface of NH2-MIL-125. The photocatalyst developed in this work performed best and gave high HFO (52%), MA (90%) selectivity, and high conversion (>90%) of furfural under various reaction conditions. The CdS (2.5%)/NH2-MIL-125 nanocomposite also showed a long-term stability. Synergistic interactions between the active surface of NH2-MIL-125 (which uses organic linkers as an antenna) and the active sites of CdS may result in enhancement of the photocatalytic activity of the CdS (2.5%)/NH2-MIL-125 photocatalyst. An analysis of the mechanism revealed that HFO and MA were produced from furfural through a series of multistep reactions, including oxidation, decarboxylation, and ring opening.